Avenger - McNab, Andy.; Rigby, Robert (London : Corgi Books, 2007)
Seventeen-year-old Danny, his grandfather, Fergus, who is an ex-SAS explosives expert, and friend Elena set out to stop the evil computer hacker who is sending teenaged suicide bombers to their deaths around the world.
Young Adult.
Young Adult
Keywords: Great Britain. -- Army. -- Special Air Service -- Fiction; Great Britain. -- Army. -- Special Air Service -- Fiction; Computer hackers -- Juvenile fiction; Grandfathers -- Juvenile fiction; Orphans -- Juvenile fiction; Revenge -- Juvenile fiction; Suicide bombings -- Juvenile fiction; Terrorism -- Juvenile fiction; Computer hackers -- Fiction; Grandfathers -- Fiction; Orphans -- Fiction; Revenge -- Fiction; Spies -- Fiction; Suicide bombings -- Fiction; Terrorism -- Fiction; Computer hackers -- Fiction; Grandfathers -- Fiction; Orphans -- Fiction; Revenge -- Fiction; Spy stories; Suicide bombers -- Fiction; Terrorism -- Fiction; Spy stories